Ketidakberdayaan Pemerintah India terhadap Isu Privatisasi Air oleh Coca-Cola tahun 1993 - 2004 - Dien Nur Rahmaniar Ungsi; Mohamad Rosyidin (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2021)
India is a mixed economic system country where the government can intervene in public affairs. Since experienced a transition period in 1991, India adopted economic liberalization policy and implemented one of the terms of economic liberalization, which is privatization in water sector. This policy led India to hand over a water sector to private companies named Coca-Cola in 1993 and it had a negative impact that is increased water crisis and environmental damage in India. The impact of water privatization by Coca-Cola is a crime that occurs as a consequence of policies that cannot be separated from the effects of adjustments to the global economic system. This research aims to explain the driving factors of the powerlessness of the Indian government in dealing with losses incurred as a result of Coca-Cola's water privatization policy in 1993-2004. The analysis in this study uses a qualitative research method with an explanative research type. This study uses Marxism theory to explain the driving factor of the powerlessness of the Indian government in dealing with the issue of Water Privatization by Coca-Cola. This study found that what prompted the powerlessness of the Indian government was influenced by two factors. First, there is a pressure from changes in domestic economic conditions that make India following global political changes as a solution to the Indian economic crisis. Second, there is a pressure from international economic institutions namely IMF and World Bank which provide loans for India, so that India implementing a structural adjustment program.